DESCRIPTION EARLY INITIATION OF BREASTFEENDING IN NEWBORN NORMALY SELFPRACTICE IN THE MIDWIE (BPM) ERRAWATI, Amd.Keb PLAWIKAN JOGONALAN KLATEN - Karunia Tyara Putri; Triwik Srimulati; Maryanti . (STIKES DUTAGAMA KLATEN, 2015)
Background : Base don the phenomena that lack of knowledge about breastfeending mothers from pregnancy through postpartum impact on maternal attitudes which willthen afect the behavior of mothers in breastfeending. Karen edmond et al study indicate Early Initiation of Breastfeending within the first 1 hour after birth lowers risk of death 22% of infants aged 0-28 days. In contrast, delay initiation increases the risk of death. Objective : To determine the implementiation ofEarly Initiation ofBreastfeending Post-Maternity in BPM Errawati, Amd.Keb, Plawikan, Jogonalan, Klaten. Research Methods: In this study the method is observation, while the cross-sectional approach is a study to study dynamics of corelation. The sampling techniques used in this study is purposive sampling is a sampling with particular consideration. Results : The results showed that as many as 17 people (68%) were male. Birth weight in this study is the most normaly of 20 people (80%). This is because most of thebaby weight is 2500 grams to 4000 grams. Conclusión : base don the results it can be concluded that most ofthe characteristics ofthe respondents were male sex with baby newborn is a succsesful Early Initiation of Breastfeending is 20 infants (80%). Infants who are not succsesful Early Initiation of Breasfeending 5 people (20%). Success Early Initiaton of Breastfeending done by the time the baby is 20 pople (80%) with a time of 1 hour. Step Early Initiation of Breastfeending have done as many as 20 respondents (80%).